Bridging the gap between CVD and COVID-19: the oxidized LDL hypothesis - Jalil Daher (Frontiers in Medicine)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is an enveloped positive sense RNA virus and the causative agent of COVID-19. The viral envelope includes the spike (S) glycoprotein which mediates the entry of the virus to the host cell. The S protein comprises the receptor binding domain (RBD) that is responsible for binding to the angiotensin-converting enzyme 2 (ACE 2) receptor on the surface of target cells. ACE 2 is highly expressed on the endothelium lining blood vessels which may explain the cardiovascular symptoms of COVID-19 patients. Emerging evidence suggests that COVID-19 and cardiovascular disease (CVD) may share important mechanisms that regulate their pathogenesis and that endothelial dysfunction (ED), which has been already shown to be tightly linked to CVD, plays an instrumental role in the pathogenesis of COVID-19 by mainly affecting the hyperinflammatory and coaguloatory states that are seen during disease progression. Meanwhile, there is also increasing evidence suggesting that COVID-19-linked ED is due to a dysregulation in lipid metabolism pathways. Of note, it has been reported that low high density lipoprotein (HDL) levels correlate with the severity of COVID-19 through a potential impairment in the antioxidant capacity of HDL which may lead to lipid oxidation and the generation of oxidized low density lipoprotein (LDL). Interestingly, we have previously shown that myeloperoxidase oxidized LDL (Mox-LDL) possesses an anti-fibrinolytic activity in endothelial cells; this may negatively affect the course of COVID-19 by increasing the chance of complications such as disseminated intravascular coagulation events and ischemic strokes. In this article, I hypothesize that targeting inflammatory dyslipidemia could be highly beneficial in treating COVID-19 patients and improving their clinical outcome.